SEBAB DAN AKIBAT PUTUSNYA PERKAWINAN MENURUT KHI DAN UU PERKAWINAN - Abdul Basit Misbachul Fitri; Alwan Eka Prasetia (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2023)
Although marriage is a strong bond in forming a family, it can be broken due to several reasons, and produce legal consequences respectively. This is regulated in positive law in Indonesia, such as KHI and the Marriage Law. Among the reasons for the dissolution of marriage bonds are divorce, court decisions and death. Meanwhile, the consequences of the dissolution of a marriage vary according to the causes, including the husband's obligation to pay mut'ah, iddah and other maintenance for ex-wives who are divorced, the obligation to undergo an iddah period for a wife whose marriage is terminated by her husband, and the existence of inheritance rights for one of the parties who left by his partner.